2014
DOI: 10.1017/s1049023x1400137x
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing the Impact of Severe Tropical Cyclone Yasi on Public Health Infrastructure and the Management of Noncommunicable Diseases

Abstract: This research demonstrated that a negative trend pattern existed between the impact of STC Yasi and other similar world cyclone events on PHI and the management of NCDs. This research provides an insight for disaster planners to address concerns of people with NCDs. While further research is needed, this study provides an understanding of areas for improvement, specifically enhancing protective PHI and the development of strategies for maintaining treatment and alternative care options, such as maintaining saf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 27 publications
0
13
0
1
Order By: Relevance
“…Lack of infrastructure and damage to existing infrastructure also contribute to increased severity of disaster impact. Tropical storms and cyclones can affect public health infrastructure by damaging equipment, interrupting services, and disrupting access to clean water (Ryan et al., ). Infrastructure that is not intended to hold rainwater is inadequate to properly protect individuals from the communicable threats of waste water from flooding and disasters (De Man et al., ; Dura et al., ).…”
Section: Resultsmentioning
confidence: 99%
“…Lack of infrastructure and damage to existing infrastructure also contribute to increased severity of disaster impact. Tropical storms and cyclones can affect public health infrastructure by damaging equipment, interrupting services, and disrupting access to clean water (Ryan et al., ). Infrastructure that is not intended to hold rainwater is inadequate to properly protect individuals from the communicable threats of waste water from flooding and disasters (De Man et al., ; Dura et al., ).…”
Section: Resultsmentioning
confidence: 99%
“…With the increasing frequency of natural disasters, it is critical to understand the immediate and medium-term health needs 8.6 (1-9) 9.0 (1-9) 8.7 (2)(3)(4)(5)(6)(7)(8)(9) of the affected population for planning medical and surgical services during a response. 6 The controversies over deployment of foreign medical teams to acute-onset disasters has increased since the earthquake in Haiti, which led to a recent World Health Organization proposal to pre-credential teams.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have demonstrated the negative effect that typhoons have on patients with noncommunicable diseases. 2 In 2013, Typhoon Haiyan (referred to as Yolanda by the Philippine Atmospheric, Geophysical, and Astronomical Services Administration [PAGASA]) was the strongest typhoon to make landfall ever recorded. Its maximum wind speed was 315 km/h, giving it a classification of a category 5 on the Saffir-Simpson hurricane scale.…”
mentioning
confidence: 99%
“…Weather-related disasters result in several days to weeks of electricity outages, displacement of people, breakdown of information sources, and lack of resources to survive (food, water, shelter, medicines, transportation, Burger and Gochfeld 2014a, 2015). Severe disasters result in emotional distress, posttraumatic stress, and other serious health effects (McLaughlin et al 2010; Shear et al 2011; Lurie et al 2015; Ryan et al 2015). …”
Section: Introductionmentioning
confidence: 99%